Campur Kode Dan Alih Kode Dalam Kanal Youtube Maudy Ayunda Dan Implikasi Terhadap Pembelajaran Bahasa Indonesia Di SMA - R, Desta Alifahsyifa; Riansi, Erwin Salpa; Devi, Ade Anggraini Kartika (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to describe the forms of code mixing and code switching on Maudy Ayunda's YouTube channel entitled "Open Cards: It turns out that Najwa Shihab and Maudy Ayunda are also BUCIN!" as well as describing the factors that cause code mixing and code switching, and describing the results of research on the implications of learning Indonesian in high school. The method used in this research is descriptive qualitative using skillful free-involved listening and note-taking techniques. The results of this research have found 80 speech data in the form of code mixing and code switching. The speech data in the form of code mixing amounts to 40 pieces of data, all of the speech is included in the form of external code mixing. Meanwhile, the total number of speech data in the form of code switching is 39 data, all of the speech is included in the form of external code mixing. The factors causing code mixing and code switching carried out by Maudy Ayunda and Najwa Shihab are due to the use of more popular terms, speaker and speaker's personality, conversation partner, topic, function and purpose, speaker and person speaking, and changes in subject matter. The results of this research will be used as implications for Indonesian language learning activities in high school to be used as examples or references for language that is not appropriate to the context in Indonesian language learning.